0019 Investigating Novel-Sleep Related Genes in Drosophila Melanogaster: A Follow Up on KOMP2 Identified Genes in Mus Musculus. (27th May 2020) - Guerriero, R; Shaw, P; O'Hara, B
Abstract: Introduction: Sleep is well-conserved across phylogeny, yet the function of sleep and its underlying mechanisms are currently poorly understood. Novel-sleep related genes were previously identified by our lab in part of the Knockout Mouse Phenotyping Program (KOMP2). This international effort generated single-gene knockouts on a Mus musculus C57BL6/NJ background and proceeded to gather data on over 200 phenotypes, including five days of baseline sleep and wake parameters. Sleep data was gathered using the non-invasive, high-throughput PiezoSleep System (Signal Solutions, LLC) which uses a piezoelectric film to gather movement data which then can be assigned to be wake or sleep. These data identified 122 novel genes that influence sleep phenotypes such as sleep duration and bout length. Methods: Homologous proteins were identified and a subset of these genes are under investigation in Drosophila melanogaster, including myosin heavy chain (Mhc) and spinophillin (Spn). Using both genetic mutants and RNAi knockdowns, the effect of gene reduction on activity profiles and sleep are being analyzed. Sleep and activity data is recorded using DAM2 monitors (TriKinetics Inc.) while being maintained on a 12:12 light:dark cycle. Results: Preliminary data analysis show that aberrations in Mhc and Spn impact sleep percentage. Both Mhc and Spn are known to be involved in structure and development of synapses. Spn is involved in the neurexin scaffolding of presynaptic neurons and also help with maintaining these synapses once formed. Synaptic reorganization and regulation is known to take place during sleep, showing a potential connection of these proteins and sleep. Conclusion: These genes that show effects on sleep in both D. melanogaster and M. musculus show a conservation of the underlying sleep machinery. Support: